Posteruption chemical evolution of a volcanic caldera lake: Karymsky Lake, Kamchatka - Taran Yuri; Inguaggiato Salvatore; Cardellini Carlo; Karpov Gennady (My University, 2013)
The 1996 short-lived subaqueous eruption at the Karymsky caldera lake suddenly changed the composition of the lake water. The lake, with a surface area of ∼10 km^2 and a volume of ∼0.5 km^3, became acidic, increased its salinity to ∼1000 mg/kg, and became dominated by SO4^2- and Ca^2+. Since the eruption, the lake chemistry has evolved in a predictable manner described by simple box model. As a result of dilution by incoming SO4-Ca-Mg-poor water, SO4, Ca, and Mg concentrations follow a simple exponential decrease with a characteristic time close to the residence time of the lake. Na, K, and Cl decrease relatively significantly slower, indicating a continuing input of these constituents into the lake that was initiated during the eruption. Thus, the dynamics of two groups of lake water solutes can be predicted by a simple box model for water and solute mass balance. Key Points Karymsky lake suddenly changed chemistry as a result of the 1996 eruption One-box dynamic model correctly describes the evolution of the lake chemistry The calculated fluxes of chemicals are in a good agreement with the field data
Keywords: 38.37.25 Вулканология; 38.61.17 Гидрогеохимия; Карымский; Kamchatka